THE APPLICATION OF HACCP (HAZARD ANALYSIS CRITICAL CONTROL POINT) IN FOOD PRODUCTION DEPARTMENT - Anisatul Auliya (Jurnal Sosial Humaniora Terapan, 2020)
This study aimed to analyze the application of HACCP (Hazard Analysis Critical Control Point) in food production specifictly in the main kitchen of Ciputra Cibubur Hotel, the purpose of this application is to ensure the food safety and healthy.  The location for this study in The main kitchen of Ciputra Cibubur Hotel, and time of this research already held in December 2018 - July 2019. The design of this study is a qualitative study. Literature review, semi-structured interview methods and survey methods have been used for collecting data. The Key Informants for this research are Executive Chef, Chef De Partie, Commis 1, Commis 1 Pastry, Commis 2, Commis 2 dan garde manger. The results of this study are the application of HACCP (Hazard Analysis Critical Control Point) principles in food processing in Ciputra Cibubur Hotel has been well implemented according to standards so it can be said that all the systems during food production in Ciputra Cibubur Hotel has been guaranteed for food security and helthy before serving to the guests.Keywords : HACCP, Food Production